Question: Simplify to a specific form


The two forms below (eqn1 and eqn2) give the same result. You can convert from eqn1 to eqn2 using the expand option but is there a way can you get Maple to simplify eqn2 back to eqn1?

( I have tried all the simplify options I know)


eqn1:= int(int(k(upsilon)*h(tau)*x(t-tau)*x(t-upsilon), tau = -infinity .. infinity), upsilon = -infinity .. infinity)


eqn2:= (int(h(tau)*x(t-tau), tau = -infinity .. infinity))*(int(k(upsilon)*x(t-upsilon), upsilon = -infinity .. infinity))




Please Wait...